2018
DOI: 10.1097/tp.0000000000002094
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Fetoprotein Slope >7.5 ng/mL per Month Predicts Microvascular Invasion and Tumor Recurrence After Liver Transplantation for Hepatocellular Carcinoma

Abstract: AFP slope increasing greater than 7.5 ng/mL per month despite locoregional therapy is associated with post-LT HCC recurrence and may serve as a surrogate for microvascular invasion. These findings support incorporating changes in the AFP into candidate selection for LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…This AFP 'slope' has been thought to be more reflective of the dynamic nature of tumor biology than just a single value. Giard et al 26 recently looked at 336 patients undergoing OLT for HCC who were within Milan criteria. Nearly all (98%) of the patients had LRT at some time prior to transplant and the AFP slope was estimated by the AFP values during this pretransplant period.…”
Section: Biomarkersmentioning
confidence: 99%
“…This AFP 'slope' has been thought to be more reflective of the dynamic nature of tumor biology than just a single value. Giard et al 26 recently looked at 336 patients undergoing OLT for HCC who were within Milan criteria. Nearly all (98%) of the patients had LRT at some time prior to transplant and the AFP slope was estimated by the AFP values during this pretransplant period.…”
Section: Biomarkersmentioning
confidence: 99%
“…Similarly, Halazun et al showed that AFP responders to LRT (e.g., AFP 200‐1000 ng/mL that decreased to <200 ng/mL with LRT) had significantly better post‐LT outcome than AFP nonresponders. Rising AFP slope of more than 7.5 to 15 ng/mL/month despite LRT also predicts poor post‐LT outcome . Additional serum marker cutoffs associated with inferior post‐LT outcome include AFP‐L3 greater than 35%, des‐γ carboxyprothrombin (DCP) greater than 400 mAU/mL (or 7.5 ng/mL), and neutrophil‐to‐lymphocyte ratio (NLR) greater than 5 (Table ), although these findings require confirmation.…”
Section: Serum Markersmentioning
confidence: 99%
“…Patients with higher baseline IGF-1, had 33% lower chance of liver recurrence and 29% lower rate of death following transplantation. The recurrence of HCC after liver transplant was associated with a poor prognosis, and identification of high-risk groups may allow tailoring of immunosuppression regimens, selection of patients for closer surveillance, or appropriate enrolment in trials of adjuvant therapy, such as sorafenib (45)(46)(47)(48)(49). To the best of our knowledge, we provide the first description of preoperative IGF-1 levels correlation with outcomes following liver transplant in an HCC population.…”
Section: Discussion Discussionmentioning
confidence: 92%